REGULATIONS FOR MANAGEMENT OF WAKF ASSETS BY STAKEHOLDERS IN TANJUNG JABUNG TIMUR REGENCY, JAMBI PROVINCE - Zainal Arifin; A. Husein Ritonga; Hadri Hasan (International Journal of Southeast Asia, 2021)
In Law Number 41 of 2004 concerning waqf and Government Regulation Number 42 of 2006 concerning the implementation of Law Number 41 of 2004 concerning waqf which regulates immovable and movable waqf to provide opportunities for those whose lives are simple but want to do good. Of the eleven City Regencies in Jambi Province, one of them is Tanjung Jabung Timur Regency. Tanjung Jabung Timur Regency has 11 sub-districts, 20 sub-districts and 73 villages (out of a total of 141 sub-districts, 163 sub-districts and 1,399 villages throughout Jambi). In 2017, the population was 222,834 people with an area of 5,445.00 km² and a population distribution of 41 people/km². The research methodology used is sociological/empirical research and uses a qualitative approach, referring to all regulations or laws and regulations relating to the legal issues under study, namely research on the norms contained in the Qur'an and Al-Hadith. The results of the study, namely the regulation of waqf property management, show that the current waqf property management regulatory system is a pattern of regulation of waqf property management which is still considered traditional-consumptive. This can be known through several aspects: Leadership, Recruitment of nazira human resources, Operationalization of empowerment, Patterns of utilization of results, and control and accountability systems.